Persistence to long-term PCSK9 inhibitors treatment and its effectiveness in familial hypercholesterolemia: data from the SAFEHEART study. (3rd October 2022) - Alonso, R; Arroyo-Olivares, R; Muniz-Grijalvo, O; Diaz-Diaz, J L; Sanchez Munoz-Torrero, J; Zambon, D; Fuentes-Jimenez, F; Romero, M J; Aguado, R; Alvarez-Banos, P; Manas, M D; Arrieta, F; et al.
Abstract: Background: Most patients with heterozygous familial hypercholesterolemia (FH) do not achieve current LDL-C goals proposed by European guidelines with conventional lipid-lowering therapy (LLT). Chronic use of PCSK9 inhibitors (PCSK9i) have shown to reduce LDL-C levels up to 61% on top of statins. Persistence to chronic LLT is important to reduce the burden of atherosclerotic cardiovascular disease (ASCVD). Purpose: To analyze persistence and effectiveness of PCSK9i in clinical practice setting in FH patients from the SAFEHEART register with long-term follow-up. Methods: SAFEHEART is an open, long-term prospective study of a cohort of subjects with molecular diagnosis of FH. Follow-up is carried out every year through a standardized phone-call to collect clinical conditions, persistence to medications, lipid profile, and cardiovascular events. This study analyses subjects ≥18 years of age on stable LLT who have received PCSK9i. Results: 696 individuals (46% females), median age 56.4 years (IQR 49–66) started with PCSK9i (49% alirocumab and 51% evolocumab). Out of them 38% had history of ASCVD, and 89% were on maximum LLT. Median LDL-C at the moment of starting PCSK9i was 145 mg/dL (IQR, 123–177), representing a poor 2016 & 2019 ESC/EAS guidelines achievement (3% and 0.1% respectively). After a median follow-up of 3.7 years (IQR, 2.3–4.8), 669 patients (96%) remained on PCSK9i treatment during entire follow-up. Only 27 patients (4%) discontinued, 5 temporarily (0.7%) and 22 permanently (3.2%). Most common reasons for PCSK9i treatment interruption were medical decision (n=6), adverse event (AE) (n=5), patient decision not related with AE (n=5) and comorbidity (n=5). Median time to permanent discontinuation was 15 months (IQR, 4–33). Median LDL-C levels observed and % of LDL-C reduction obtained after 1 year of treatment and in the last follow-up visit were: 63 mg/dL (IQR, 43–88), 61 mg/dL (IQR, 44–82), 57.6% (IQR, 39.5–69) and 58% (IQR, 44–68), respectively. 2016 ESC/EAS guidelines LDL-C goals was achieved by 70% of patients at year 1 and 77% in the last follow-up visit after the introduction of PCSK9i (p<0.001). 2019 ESC/EAS goals were achieved by 44.5% and 48% (p=0.1). Conclusion: Long-term persistence to PCSK9i treatment in FH patients is very high (96%) and reasons for discontinuation are diverse. This study shows that COVID-19 pandemic did not affected persistence to treatment. Effectiveness in LDL-C reduction and LDL-C goal achievement improved significantly with introduction of PCSK9i in clinical practice setting. Funding Acknowledgement: Type of funding sources: Private grant(s) and/or Sponsorship. Main funding source(s): AMGEN